Uso de calorimetria para estimativa da distribuição do calor gerado no processo de furação de ferro fundido - Costa, Ivanilson Sousa da (2019)
The heat generated and the temperature distribution in machining greatly influence cutting tool wear, surface integrity and dimensional accuracy of machined parts, so that heat and temperature generation phenomena have been investigated by experimental, analytical and numeric methodologies. This thesis aimed to determine the amount of heat generated in the gray cast iron drilling through the calorimetric method. The calorimeter employed consisted of two coaxial cylindrical boxes made of Polyamide 6.6 and Polyvinyl Chloride. T-type thermocouples were used to continuously measure the temperatures of the calorimetric fluid. Calorimeter equation was defined for the methodology applied. Calorimeter was also used to measure the heat transfer to the drill bit, the heat transfer to the chips and the temperature of drill bit and chips. The temperature distribution during the cutting were measured experimentally by infrared measurement and simulated by the finite element method with the AdvantEdgeTM software. It has been shown that between 82.63 % and 83.46 % of the mechanical energy spent for the cutting was converted into heat during machining. Calorimetric method presented results consistent with the literature, thereby, confirming the applicability of the methodology employed to evaluate the mechanical energy transformed into thermal energy in machining. Finite element method has proved to be an effective tool in simulation tests of the drilling process. On the other hand, infrared thermography presented limitations when associated with the calorimetric method.